The use of active methodologies in remote teaching during the COVID-19 pandemic (Research, Society and Development, 2022)
Faced with the COVID-19 pandemic, educational institutions had their classes suspended, affecting thousands of students around the world. In an attempt to minimize educational losses, Emergency Remote Teaching (ERE) emerged, which had as an essential resource the use of Digital Information and Communication Technologies (DICTs) to provide student participation through the use of Active Methodologies (AM). In this context, the present study aimed to investigate in the literature, through an integrative review, the use of Active Methodologies in the teaching-learning process during distance learning in the pandemic period. Among the selected works, 6 studies addressed the importance that AM played in maintaining students' critical thinking, even outside the school environment. In this way, it became evident that the use of Active Methodologies in the ERE in the pandemic acted as a potentiating agent of the teaching-learning process, but with weaknesses related to the difficulty of using technologies, as well as the lack of access to the necessary resources.